Wpływ nowych koncepcji zarządzania na rozwój przedsiębiorstwa. Doświadczenia praktyczne - Prus, Janusz (The Influence of New Management Conceptions on an Enterprise Development : Empirical Study, 2006)
The article characterizes the development process of a company and presents activities that enable implementation of new concepts and management methods. It must be emphasized that this is an outstandingly empirical study that shows reasons of improving management in the company and possible ways of bringing new management methods into action.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 489-499